The masque of Africa : glimpses of African belief - Naipaul, V. S. (Vidiadhar Surajprasad), 1932-2018. (New York : Alfred A. Knopf, 2010)
Nobel Prize-winning author Naipaul spirals outward from the central African country of Uganda, to Nigeria, Ghana, the Ivory Coast, Gabon, and concluding in South Africa, to unearth in six chapters a sense of African ancestral belief and practice.
The tomb at Kasubi -- Sacred places -- Men possessed -- The forest king -- Children of the old forest -- Private monuments, private wastelands.
Keywords: Africa -- Religion; Africa -- Description and travel